Acquired cholesteatoma epithelial hyperproliferation: Roles of cell proliferation signal pathways. (15th March 2016) - Xie, Shumin; Xiang, Yuyan; Wang, Xiaoli; Ren, Hongmiao; Yin, Tuanfang; Ren, Jihao; Liu, Wei
Abstract : Objectives/Hypothesis: To review the recent cell proliferation signal pathways in the etiopathogenesis of acquired middle ear cholesteatoma. Data Sources: PubMed (to September 2015). Review Methods: Articles about cell proliferation signal pathways in the etiopathogenesis of acquired cholesteatoma and treatment advances were searched in the PubMed database, from which 73 were included in this review. Results: The exact underlying cellular and molecular mechanism of acquired cholesteatoma still remains unknown. Recent research tends to regard the proliferation of cholesteatoma epithelial cells as the mechanism of cholesteatoma pathogenesis. Cell proliferation signal pathways including epidermal growth factor receptor/phosphoinositide 3‐kinase/protein kinase B signal pathway, mitogen‐activated protein kinase signal pathway, interleukin‐6/signal transducer and activator of transcription 3 signal pathway, inhibitor of DNA binding/differentiation‐1/nuclear factor‐κB/cyclinD1 signal pathway, microRNA‐mediated proliferation signal pathway, and keratinocyte growth factor/keratinocyte growth factor receptor signal pathway have been proven to play important roles in acquired middle ear cholesteatoma. Conclusions: This review outlines the main biological properties of certain cell proliferation signal pathways, aiming to facilitate the development of potential therapeutic targets for intratympanic drug therapy for the nonsurgical or complementary treatment of cholesteatoma. Level of Evidence: NA Laryngoscope, 126:1923–1930, 2016